Chinese Guanxi: An Integrative Review and New Directions for Future Research. 中国人的关系: 综合文献回顾及未来研究方向. (1st March 2013) - Chen, Chao C.; Chen, Xiao‐Ping; Huang, Shengsheng
<x xml:space="preserve">Abstract</x> Abstract In this article we review research on Chinese guanxi and social networking in the past twenty years and identify the major perspectives, theories, and methodologies used in guanxi research at micro and macro levels. We summarize the main findings of over 200 journal articles on guanxi research in terms of its conceptual definitions and measurements, its antecedents and consequences, and its dynamics and processes. Furthermore, we identify the gaps between different levels of guanxi research and discuss future directions to advance our understanding of the complex and intricate guanxi phenomenon. 摘要 本文综合回顾了过去二十年来中外文献中有关中国人关系和社会网络的研究，对微观及宏观层次上关系研究的主要视角、理论、及研究方法进行了区分，并对关系研究在概念定义、测量、前因后果、动态变化和过程等方面的主要实证研究结果进行了总结。此外，本文论述了不同层次关系研究之间的空白并指出了未来研究方向, 以便更深入全面地探讨和了解关系现象的错综复杂性。